Integrating Environmental Education Into Science Learning to Foster Environmental Awareness: A Case Study of An Adiwiyata Madrasah Ibtidaiyah - Wildatis Saidah Kholidiyah; Rizqiyah Ratu Balqis (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study examines the integration of Environmental Education in Natural Science learning at Madrasah Ibtidaiyah Assunniyyah 45 Paseban, an Adiwiyata-certified Islamic primary school in Jember, East Java, Indonesia. Employing a qualitative case study approach, data were collected through semi-structured interviews with the school principal, science teachers, and the Adiwiyata coordinator, supplemented by classroom observations and document analysis. The study reveals three main findings, encompassing the integration of environmental education in science learning, the role of teachers in integrating environmental education into science instruction, and the enabling and inhibiting factors that shape the integration process. The findings demonstrate that the Adiwiyata school environment functions as a living laboratory that transforms abstract ecological concepts into concrete, value-laden learning experiences. These findings provide empirical evidence regarding the integration of environmental education in Islamic primary education, a context that remains largely absent from the existing international literature.